Membangun Masyarakat Digital Yang Beretika: Mengintegrasikan Nilai-Nilai Kristen Di Era Teknologi Digital 5.0 - Waruwu, Elfin Warnius; Lawalata, Mozes (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
The rapid development of digital technology 5.0 presents major challenges for Christians and creates conflict between Christian values ​​and rapidly developing technological practices. This research aims to analyze the relevance of Christian values ​​in the context of Technology 5.0 and discuss integration strategies in digital society. Increased use of technology leads to increased human and social awareness and rational responses, which creates uncertainty that needs to be addressed. Using qualitative methods, this research will explain how Christian values ​​such as honesty, justice, and love are still present in the dynamics of an interconnected digital society. In addition, this research discusses integration strategies that can be carried out by individuals, groups, churches, and Christian organizations so that these values ​​are not only recognized but also applied in everyday life. This study focuses on a deeper understanding of the impact of technology on Christian values, providing concrete solutions to overcome ethical and moral challenges in a digital society. Through collaboration between church leaders, technology experts, and Christian community members, this research aims to lay the foundation for digital social change, creating an environment that demonstrates Christian ethical and moral obligations in the era of Digital Technology 5.0.